Aortic enlargement in chronic obstructive pulmonary disease (COPD) and emphysema: The Multi-Ethnic Study of Atherosclerosis (MESA) COPD study. (15th May 2021) - Fujikura, Kana; Albini, Alessandra; Barr, R. Graham; Parikh, Megha; Kern, Julia; Hoffman, Eric; Hiura, Grant T.; Bluemke, David A.; Carr, James; Lima, João A.C.; Michos, Erin D.; Gomes, Antoinette S.; et al.
Abstract: Background: The prevalence of abdominal aortic aneurysm is high in chronic obstructive pulmonary disease (COPD) population. Emphysema involves proteolytic destruction of elastic fibers. Therefore, emphysema may also contribute to thoracic aorta dilatation. This study assessed aorta dilation in smokers stratified by presence of COPD, emphysema and airway thickening. Methods: Aorta diameters were measured on 3D magnetic resonance angiography in smokers recruited from the Multi-Ethnic Study of Atherosclerosis (MESA), the Emphysema and Cancer Action Project (EMCAP), and the local community. COPD was defined by standard spirometric criteria; emphysema was measured quantitatively on computed tomography and bronchitis was determined from medical history. Results: Participants ( n = 315, age 58–79) included 150 with COPD and 165 without COPD, of whom 56% and 19%, respectively, had emphysema. Subjects in the most severe quartile of emphysematous change showed the largest diameter at all four aorta locations compared to those in the least severe quartiles (all p < 0.001). Comparing subjects with and without COPD, aorta diameters were larger in participants with severe COPD in ascending and arch (both p < 0.001), and abdominal aorta ( p = 0.001). Chronic bronchitis and bronchial wall thickness did not correlate with aorta diameter. In subjects with emphysema, subjects with coexistence of COPD showed larger aorta than those without COPD in ascending ( p = 0.003), arch ( p = 0.002), and abdominal aorta ( p = 0.04). Conclusions: This study showed larger aorta diameter in subjects with COPD and severe emphysema compared to COPD related to chronic bronchitis or bronchial wall thickening. Highlights: Comparing subjects with and without COPD, aorta diameters were larger in participants with severe COPD. In subjects with emphysema, subjects with coexistence of COPD showed larger aorta than those without COPD. Chronic bronchitis and bronchial wall thickness did not correlate with aorta diameter.